Implementation of Regional Regulation No. 3 of 2005 concerning Zakat in the Development of Micro Enterprises in Bantaeng Regency - Mahendra, Yusril Ihza; Mustafa, Zulhasari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The main problem in this study examines how the efforts of the regional government of Kab. Bantaeng in implementing regional regulation no 3 of 2005 concerning the management of zakat? How zakat funds are empowered for the development of micro-enterprises in Kab. Bantaeng? This study aims to determine Zakat Management in the Development of Mustahik Micro Enterprises in Kab. Bantaeng. The type of research used is a qualitative research method with a descriptive research type. Data collection techniques using observation, interviews, and documentation. The results of the study show that 1) the efforts of the regional government of Kab. Bantaeng in implementing regional regulation no 3 of 2005 concerning zakat management namely zakat collection, distribution, utilization, reporting and accountability. 2) zakat funds are empowered for the development of micro-enterprises in Kab. Bantaeng is like providing business capital to MSMEs engaged in grobak businesses around the mosque.